Incidental and simultaneous finding of pulmonary thrombus and COVID-19 pneumonia in a cancer patient derived to 18F-FDG PET/CT. New pathophysiological insights from hybrid imaging (2020)
Cancer patients require a careful clinical follow-up during the coronavirus disease 2019 (COVID-19) pandemic. Although hybrid fluorine-18 Fluorodeoxyglucose ( 18F-FDG) positron emission tomography-computed tomography (PET/CT) is not routinely used in the management of COVID-19 patients, it could play a complementary role of other laboratory and radiological data in selected cases. We describe an asymptomatic cancer patient derived to 18F-FDGPET/CT with simultaneous findings of COVID-19 pneumonia and pulmonary thrombus, discussing its possible mechanisms and prognostic implications